Can enhanced feedback effects and improved breeding coincide in a metal fueled, sodium cooled fast reactor?. (July 2017) - Merk, B.; Devan, K.; Bachchan, A.; Paul, D.; Puthiyavinayagam, P.; Srinivasan, G.
Highlights: An innovative fuel assembly design has been studied in detail. Arrangement of fertile rods within the fuel assembly can improve breeding. Fine distributed moderating material enhances feedback effects. Abstract: The sensitivity of operational and safety parameters on different strategies for the improvement of in core breeding on fuel assembly level are investigated using the HELIOS 2.1 code. The operational characteristics is analyzed regarding criticality, breeding, pin power and burnup distribution. As additional key parameters, the conservation of the safety related feedback effects of the assembly are examined. It is demonstrated that the insertion of 1/3 of fertile fuel rods into the fuel assembly, while the overall Pu content of the assembly is kept constant, can improve the breeding of fresh plutonium. A second proposal is the reduction of the initial Pu content of the assembly which is compensated by eliminating one ring of the fertile blanket around the core. This method proofs to be very efficient to improve the in-core breeding. The consequences on the fuel assembly multiplication factor, the fissile material content, and the pin wise power as well as burnup distribution is analyzed. Additionally, the effect of fine distributed material on breeding as well as on the safety related feedback effects is investigated for both proposals. A clear enhancement of the feedback effects is proven.